Antimicrobial Therapy Duration for Bloodstream Infections Caused by Pseudomonas aeruginosa or Acinetobacter baumannii-calcoaceticus complex: A Retrospective Cohort Study - Rodrigo Douglas Rodrigues; Rebeca Carvalho Lacerda Garcia; Gabriel Almeida Bittencourt; Vicente Bouchet Waichel; Ester Carvalho Lacerda Garcia; Maria Helena Rigatto (Antibiotics, 2023)
Background: Ideal therapy duration for Pseudomonas aeruginosa or Acinetobacter baumannii-calcoaceticus complex (ABC) bloodstream infections (BSI) is not defined, especially in the context of carbapenem resistance. In this study, we compared short- (≤7 days) and long-term (>7 days) antimicrobial therapy duration for these infections. Methods: We performed a retrospective cohort study in two tertiary-care hospitals in Porto Alegre, Brazil, from 2013 to 2019. Eligible patients aged ≥18 years were included and excluded for the following criteria: polymicrobial infections, treatment with non-susceptible antibiotics, complicated infections, or early mortality (<8 days of active antimicrobial therapy). The 30-day mortality risk was evaluated using a Cox regression model. Results: We included 237 BSI episodes, 51.5% caused by ABC and 48.5% by Pseudomonas aeruginosa. Short-term therapy was not associated with 30-day mortality, adjusted hazard ratio 1.01, 95% confidence interval 0.47–2.20, p = 0.98, when adjusted for Pitt score (p = 0.02), Charlson Comorbidity Index score (p < 0.01), and carbapenem resistance (p < 0.01). Among patients who survived, short-term therapy was associated with shorter hospital stay (p < 0.01). Results were maintained in the subgroups of BSI caused by carbapenem-resistant bacteria (p = 0.76), ABC (p = 0.61), and Pseudomonas aeruginosa (p = 0.39). Conclusions: Long-term therapies for non-complicated Pseudomonas aeruginosa and ABC BSI were not superior to short-term therapy for 30-day mortality.